Body composition predictors of therapy response in patients with primary extremity soft tissue sarcomas. (April 2018) - De Amorim Bernstein, Karen; Bos, Stijn A; Veld, Joyce; Lozano-Calderon, Santiago A; Torriani, Martin; Bredella, Miriam A
Background: Recent studies have suggested that the quantity and quality of adipose tissue and muscle, assessed on non-contrast computed tomography (CT), may serve as imaging biomarkers of survival in patients with and without neoplasms. Purpose: To assess body composition measures that could serve as predictors of therapy response in patients with extremity soft tissue sarcomas treated with radiation therapy and surgery. Material and Methods: The study was IRB-approved. Sixty patients had a history of extremity soft tissue sarcoma and underwent FDG-PET/CT prior to radiation therapy and surgical resection. Cross-sectional areas and CT attenuation (HU) of abdominal subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), and psoas muscle were assessed on non-contrast CT. Clinical information on predictors of tumor recurrence and post-surgical wound infections were recorded. Cox proportional hazard models were used to determine longitudinal associations between body composition and tumor recurrence/wound infections. Results: Twenty-three tumor recurrences occurred over a follow-up period of 43 ± 35 months. Higher SAT and lower psoas attenuation were associated with tumor recurrence which remained significant after adjustment for covariates ( P  ≤ 0.01). There were 13 post-surgical wound infections. Higher VAT and SAT attenuation were associated with post-surgical wound infections ( P  < 0.04); however, VAT attenuation lost significance after adjustment for covariates. Conclusion: Abdominal adipose tissue and psoas muscle attenuation assessed on non-contrast CT may predict tumor recurrence and post-surgical infections in patients with extremity soft tissue sarcomas.